Comparison of MRI T2-lesion evolution in pediatric MOGAD, NMOSD, and MS. (June 2023) - Redenbaugh, Vyanka; Chia, Nicholas H; Cacciaguerra, Laura; McCombe, Jennifer A; Tillema, Jan-Mendelt; Chen, John J; Lopez Chiriboga, A Sebastian; Sechi, Elia; Hacohen, Yael; Pittock, Sean J; Flanagan, Eoin P
Background: Magnetic resonance imaging (MRI) T2-lesions resolve more often in myelin oligodendrocyte glycoprotein (MOG) antibody-associated disease (MOGAD) than aquaporin-4 IgG-positive neuromyelitis optica spectrum disorder (AQP4 + NMOSD) and multiple sclerosis (MS) in adults but few studies analyzed children. Objective: The main objective of this study is to investigate MRI T2-lesion evolution in pediatric MOGAD, AQP4 + NMOSD, and MS. Methods: Inclusion criteria were as follows: (1) first clinical attack; (2) abnormal MRI (⩽6 weeks); (3) follow-up MRI beyond 6 months without relapses in that region; and (4) age < 18 years. An index T2-lesion (symptomatic/largest) was identified, and T2-lesion resolution or persistence on follow-up MRI was determined. Results: We included 56 patients (MOGAD, 21; AQP4 + NMOSD, 8; MS, 27) with 69 attacks. Index T2-lesion resolution was more frequent in MOGAD (brain 9 of 15 [60%]; spine 8 of 12 [67%]) than AQP4 + NMOSD (brain 1 of 4 [25%]; spine 0 of 7 [0%]) and MS (brain 0 of 18 [0%]; spine 1 of 13 [8%]), p < 0.01. Resolution of all T2-lesions occurred more often in MOGAD (brain 6 of 15 [40%]; spine 7 of 12 [58%]) than AQP4 + NMOSD (brain 1 of 4 [25%]; spine 0 of 7 [0%]), and MS (brain 0 of 18 [0%]; spine 1 of 13 [8%]), p < 0.01. Reductions in median index T2-lesion area were greater in MOGAD (brain, 305 mm; spine, 23 mm) than MS (brain, 42 mm [ p <0.001]; spine, 10 mm [ p <0.001]) without differing from AQP4 + NMOSD (brain, 133 mm [ p =0.42]; spine, 19.5 mm [ p =0.69]). Conclusion: In children, MRI T2-lesions resolved more often in MOGAD than AQP4 + NMOSD and MS which is similar to adults suggesting these differences are related to pathogenesis rather than age.